Magnetic Topological Semimetal Phase with Electronic Correlation Enhancement in SmSbTe. Issue 10 (24th August 2021) - Pandey, Krishna; Mondal, Debashis; Villanova, John William; Roll, Joseph; Basnet, Rabindra; Wegner, Aaron; Acharya, Gokul; Nabi, Md Rafique Un; Ghosh, Barun; Fujii, Jun; Wang, Jian; Da, Bo; et al.
Abstract: The ZrSiS family of compounds hosts various exotic quantum phenomena due to the presence of both topological nonsymmorphic Dirac fermions and nodal‐line fermions. In this material family, the LnSbTe (Ln = lanthanide) compounds are particularly interesting owing to the intrinsic magnetism from magnetic Ln which leads to new properties and quantum states. In this work, the authors focus on the previously unexplored compound SmSbTe. The studies reveal a rare combination of a few functional properties in this material, including antiferromagnetism with possible magnetic frustration, electron correlation enhancement, and Dirac nodal‐line fermions. These properties enable SmSbTe as a unique platform to explore exotic quantum phenomena and advanced functionalities arising from the interplay between magnetism, topology, and electronic correlations. Abstract : The layered magnetic topological semimetal SmSbTe exhibits a rare coexistence of multiple functional properties including 4 f ‐magnetism, a possible magnetic frustration and Kondo effects, electronic correlation enhancement, and Dirac nodal‐line fermions. The combination of these properties in a single material system provides a promising platform to explore new topological states and applications.